Spatial shift in China's labor struggles: Evidence and implication. (18th February 2019) - Xu, Zhun; Chen, Ying
Abstract : With the slowdown of capital accumulation in the past few years in China, accompanied labor struggles begin to move geographically and experience transformation in their forms. Based on detailed empirical analysis, we highlight a discernible spatial shift of labor conflicts from the coastal regions to the inner regions. Meanwhile, repression of labor struggles is becoming more aggressive and violent and hence we are observing the end of the short‐lived Golden Age period of labor activism in the coastal regions. We further argue that, as the capital accumulation expands in the inner regions, the current seemingly tranquil capital‐labor relation is only temporary.